PENGARUH PENAMBAHAN VANADIUM OKSIDA (V2O5) TERHADAP STRUKTUR KRISTAL Ba 0.9 Ca0.1TiO3 - Rizky N; Suasmoro Suasmoro (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
Barium calsium titanate (BCT) is one of perovskite’s crystal structure and has polimorfism to temperature. Composition of BCT was synthesized via oxalate coprecipitation precursor. The powder was V5+ doped by 0; 0.5 and 1 mole %. It was analyzed by thermal analysis. Single phase of BCT was formed at calcination temperature 7000C for 2 hours. The powder was compacted and pelleted. To decrease porous sample sintered at temperature 13000C for 2 hours. Vanadium doped can decrease temperature of sinter to be 12500C. The influences of dopant on samples were analyzed by XRD. Tetragonallity of sample that undoped is 1.0031 and doped V5+ 0.5 % is 1.0026 and doped V5+ 1 % is 1.0019. Characterization on crystal structure show that V5+ subtituted into Ti4+ sites to form single phase of BCT. Keywords: BCT, copresipitation, vanadium, single phase.